Creatine kinase and SLCO1B1 RS4363657 polymorphism in Malaysian dyslipidaemic patients prescribed with statin drugs - Meor Anuar Shuhaili, Meor Fairuz Rizal (2016)
Background: Statin, a first line treatment for dyslipidaemia has reduced patient compliance and is underprescribed because of its side effect of muscle toxicity. The incidence of statin-induced muscle toxicity ranges from 1% to 7%, whereas severe muscle toxicity occurs in up to 0.5% of patients. In Malaysia, however, this data remains limited, due to under-reported, mis/underdiagnosed cases or statin-induced muscle toxicity is generally rare. Aim: The aim of this study is to analyse the association of serum creatine kinase (CK) and rs4363657 polymorphism of SLCO1B1 gene with statin-induced muscle toxicity, and the lipid-lowering effects of different type of statins (simvastatin and lovastatin) prescribed among dyslipidaemia patients. Methodology: This was a prospective cohort study involving 118 newly diagnosed adult patients with dyslipidaemia who were prescribed a statin for the first time. Statininduced muscle toxicity was recorded based on the complaint of muscle aches and pains on follow-up after 1 month on statin. Biochemical analyses (CK, fasting lipid profile, apo A1, apo B) were done on the first and follow-up appointments. Genetic profiling was done for rs4363657 polymorphism of SLCO1B1 gene. Data was analysed using IBM SPSS Statistics version 22.0 for Windows. Results: The study showed significance difference in the effect of lovastatin and simvastatin on all lipid profile parameters (TC, HDL-C, LDL-C, LDL:HDL, non-HDLC, TC:HDL, apo A1, apo B, apo B:apo A1) except for TG (p<0.05). By comparing median change in lipid values between first and follow up appointments, simvastatin had a significantly greater effect than lovastatin. There was significant association between types of statin prescribed with statin-induced muscle toxicity (p = 0.0327); frequency of muscle aches and pains being higher with lovastatin compared to simvastatin (15.25% vs 3.39%). However, there was no significance relationship between CK level with statin-induced muscle toxicity (p = 0.5637). The rs4363657 polymorphism of SLCO1B1 gene was significantly associated with statin-induced muscle toxicity (p<0.0001). The frequency of statin-induced muscle toxicity was highest in CC genotype (100%) followed by TC genotype (42.31%) and TT (wild type) genotype (3.57%). Patients with TC genotype and CC genotype are 26.241 times and 357.964 times more likely to exhibit statin-induced muscle toxicity than patients with normal SLCO1B1 gene, respectively (p<0.0001). Conclusion: Simvastatin had a better effect compared to lovastatin in improving all lipid parameters, including predictors of CVD risks. However, muscle toxicity was more significant in patients prescribed with lovastatin compared to simvastatin. CK was shown to be not a significant biomarker to indicate muscle toxicity. It can be concluded that SLCO1B1 gene is a good genetic marker for statin-induced muscle toxicity. The only significant risk factor for statin-induced muscle toxicity in this study was rs4363657 polymorphism of SLCO1B1 gene.